The Influence of Principal Leadership and Work Motivation on Teacher Performance at Elementary School - Anita, Anita; Chairilsyah, Daviq; Kartikowati, Sri (Journal of Educational Sciences, 2022)
Teacher performance or work performance is the result achieved by the teacher in carrying out the tasks assigned to him based on skills, experience and sincerity as well as the use of time. The other is including the lack of teacher motivation in teaching and doing their job, the lack of teacher dedication to advancing the school and assisting students in achieving both in competitions and in the Olympics. Besides, an unsupportive work climate, lack of teacher discipline, and there are still many teachers who do not make preparations in teaching are also found in the field. This study uses a descriptive correlational research method with a quantitative approach. The population of this study were teachers of State Elementary Schools 10, 12, 23, and 35 totaling 44 people. The sampling technique in this study used a saturated sample, so all the population of 44 teachers was the sample. The results of this study, partially or individually there is the influence of the principal's leadership on teacher performance at SDN Rupat District.